Neuropsychiatric effects of low exposure to styrene. Issue 11 (November 1989) - Flodin, U; Ekberg, K; Andersson, L
Abstract : Workers exposed to styrene concentrations of about 50 mg/m3 at a plant manufacturing reinforced polyester boats were examined for neuropsychiatric symptoms both in close connection with exposure and also seven months after exposure had ceased. Physical workload is important for the uptake of styrene and was about 50 W at this plant. On the first occasion, after one week with no exposure, the workers reported a high frequency of neuropsychiatric symptoms such as fatigue, irritation, and forgetfulness whereas seven months later the frequency of these symptoms was low. These observations indicate that exposure to styrene at about 50 mg/m3 may induce reversible neuraesthenic symptoms. Even the relatively low Swedish standard (110 mg/m3 = 25 ppm) may, therefore, need revising.